2012
DOI: 10.1177/1538574411431345
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Local and General Anesthesia for Carotid Endarterectomy: Early and Late Results

Abstract: Despite the lack of significant difference between LA and general anesthesia in terms of restenosis, neurological events, and death in the long-term period; LA is more preferable due its associated advantages including availability of testing the consciousness of the patients by direct contact, reduced use of shunts, shorter hospitalization periods, and less prevalence of permanent stroke in the short-term period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…and deaths were similar in the 2 groups at long-term follow-up (48) . However, the rate of shunt placement as well as operative time was lower in LA group than the general anesthesia group.…”
Section: Review Articlementioning
confidence: 69%
“…and deaths were similar in the 2 groups at long-term follow-up (48) . However, the rate of shunt placement as well as operative time was lower in LA group than the general anesthesia group.…”
Section: Review Articlementioning
confidence: 69%
“…Research has shown local anaesthetic to be safe and efficient for internal carotid endarterectomy (26). Gurer and colleagues showed that it reduced operation time, shunt usage, hospitalisation time and permanent stroke rates in this procedure (27). 23 patients underwent TAVI via carotid access under local anaesthetic in this systematic review.…”
Section: Surgical Technique and Equipmentmentioning
confidence: 81%
“…It also allowed for a 'cross-clamp test' to be performed, which if failed, allowed the placement of a temporary carotid shunt similar to standard carotid endarterectomy practice under local anaesthetic (26,27). route, but also subclavian and transaortic) (28).…”
Section: Neurological Complicationsmentioning
confidence: 99%
“…Literature searches of the databases identified 1294 articles. Following the screening of retrieved titles or abstracts and after assessing the full texts of relevant reports, we selected 33 articles for analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%